English Vocabulary Mastery of University Students an Analysis Of Students’ Essays Writing at Bina Bangsa Getsempena University - Qamariah, Hijjatul; Sabarniati, Sabarniati (IJET (Indonesian Journal of English Teaching), 2023)
Without doubt, vocabulary is a crucial part in mastering English language skills. It is the basic element that helps to construct a well written or spoken text. These two production skills assist students to be communicative well. However, the range of vocabulary produced becomes a problem when the students have difficulties to deploy the words properly. This study, therefore, tried to examine the typical of vocabulary applied by the EFL students in their writing text. By analyzing those writing text, it is depicted the vocabularies they applied. This is a qualitative descriptive research. The researchers relied on the list of academic words by Averil Coxhead (2000) and new academic words by Dr. Charles Browne, Dr. Brent Culligan and Joseph Phillips (2013) in analyzing the vocabularies in the written text. The words in the written texts were highlighted and categorized based on the lists. The result showed that, the students’ vocabularies had some characteristics: (1) low lexical density; (2) higher repetition of information; and (3) higher proportion of basic and frequently-used words and lower usage of academic words. Therefore, it is suggested that students need more exposure to AWL or NAWL, there is Vocabulary development assistance and vocabularies should be taught contextually.